Pengaruh Keputusan Investasi, Keputusan Pendanaan dan Ukuran Perusahaan Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Properti dan Real Estat Yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019) - Fernando Galih Prasetyo (Borobudur Management Review, 2021)
This study aims to examine and analyze the effect of investment decisions, funding decisions, and firm size on firm value in Real Estate and Real Property companies on the IDX in 2015-2019. The research method carried out in this study using purposive sampling method and obtained a sample of 15 companies. Hypothesis testing is done by using multiple linear regression analysis. The results of the study prove that investment decisions have a positive effect on firm value, funding decisions have a positive effect on firm value and firm size has a negative effect on firm value.